A notational analysis of shot characteristics in top-level table tennis players - Malagoli Lanzoni, I.; Di Michele, R.; Merni, F. (European Journal of Sport Science, 2014)
This study aimed to analyse selected shot characteristics in top-level table tennis matches, with a special focus on comparing the playing style of Asian and European players. Ten men's matches played by 20 top-ranked players (14 Asians and 6 Europeans) were analysed. The indicators examined were the area of ball bouncing for serves (n =918), and the stroke type, footwork type and shot outcome for other shots (n=3692). The interrelationships between variables were analysed using chi-squared tests, log-linear modelling and multiple correspondence analysis. A strong association was found between strokes and footwork types, with most stroke types executed each after specific footwork types. Furthermore, a clear tendency to have a positive, negative or neutral outcome was observed for each stroke type. When compared to Europeans, Asians used more frequently the most aggressive strokes and footwork types, confirming anecdotal claims on their particularly offensive playing style. Asians showed also a better serving effectiveness, often sending the ball in those areas of the table from which a counterattack is difficult to make. In summary, this study gives a systematic description of highly relevant technical and tactical characteristics in top-level table tennis, thus providing valuable information for coaches and performance analysts.